2023
DOI: 10.1111/tpj.16140
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the phosphate starvation response sheds light on strigolactone biosynthesis in rice

Abstract: SUMMARY Phosphorus (P) is a major element required for plant growth and development. To cope with P shortage, plants activate local and long‐distance signaling pathways, such as an increase in the production and exudation of strigolactones (SLs). The role of the latter in mitigating P deficiency is, however, still largely unknown. To shed light on this, we studied the transcriptional response to P starvation and replenishment in wild‐type rice and a SL mutant, dwarf10 (d10), and upon exogenous application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 90 publications
(130 reference statements)
0
22
0
Order By: Relevance
“…At each combination of growth condition and time point, the root transcriptome of three new plants was harvested for RNA sequencing. In this dataset, the curated list of SL pathway genes (contained in Supplementary Table 1) shows a specific profile: low variance baseline expression across all time points in the P+ condition but activation and increasing expression over time with P starvation, data were generated and preprocessed to variance stabilised counts as per (5).…”
Section: Rnaseq -Rice Strigolactone Dataset (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…At each combination of growth condition and time point, the root transcriptome of three new plants was harvested for RNA sequencing. In this dataset, the curated list of SL pathway genes (contained in Supplementary Table 1) shows a specific profile: low variance baseline expression across all time points in the P+ condition but activation and increasing expression over time with P starvation, data were generated and preprocessed to variance stabilised counts as per (5).…”
Section: Rnaseq -Rice Strigolactone Dataset (5)mentioning
confidence: 99%
“…The interaction between these two pathways has been characterised recently under nitrogen limitation by (24). transformed expression level of one of the bait genes (CCD8), y axes; expression levels of three example coexpression candidates for each method (see (5) for preprocessing details).…”
Section: Real Data Applicationsmentioning
confidence: 99%
“…The homologues of SL biosynthetic genes in pearl millet PgD27 ( PgP10c0101G011332 ), PgCCD8 ( PgP10c0601G021829 ), PgMAX1 - 1400 ( PgP10c0601G022366 ), PgCYP706 ( PgP10c0401G051155 ) and PgCLAMT1b ( PgP10c0201G045110 ) (Supplementary figures 8, 9, 10) were all markedly upregulated in P10 under low Pi conditions (over 32-fold) and further by MP3 treatment. The canonical SL analog GR24 suppresses SL biosynthetic genes in rice, even under Pi deficiency (Haider et al, 2023). Therefore, the unexpected increase in expression observed here may be because MP3, a non-canonical SL analog, acts differently from GR24, or because SL biosynthesis is regulated differently in pearl millet compared to rice.…”
Section: Main Textmentioning
confidence: 99%
“…Notably, CLAMT1b was absent in the Aw genome, as were CLAMT1c ( PgP10c0201G045096.1 ), a CYP51 homolog and a putative acyl transferase encoded by the 0.7 Mb fragment present in P10 (Figure 2b). CLAMT enzymes, involved in SL biosynthesis in rice and maize (Haider et al, 2023; Li et al, 2023), convert carlactonoic acid (CLA) into methyl carlactonoate (MeCLA) (Mashiguchi et al, 2022) in the formation of non-canonical SLs. In pearl millet, we identified three CLAMT genes with differing responses to phosphate starvation and MP3 treatment.…”
Section: Main Textmentioning
confidence: 99%
“…It has been recently shown that a complex gene network centered on the plant Pi starvation response actively supervises AM fungal development in roots, acting at the local and systemic level (Shi et al ., 2021; Das et al ., 2022). Pi starvation also induces SL biosynthesis and release (Yoneyama et al ., 2007; Wang et al ., 2017, 2022), while high Pi levels repress the expression of genes involved in the biosynthesis of carotenoids and SLs in root (Carbonnel and Gutjahr, 2014; Haider et al ., 2023). SLs are the best-known plant molecules active in the pre-symbiotic interaction with AM fungi.…”
Section: Introductionmentioning
confidence: 99%